2003
DOI: 10.1161/01.hyp.0000049760.15764.2d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Severe Hypertension on Endothelial and Platelet Microparticles

Abstract: Abstract-The molecular mechanisms by which extreme blood pressure elevation leads to vascular injury are not defined.To explore the hypothesis that activation of endothelium and platelets as manifested by increased concentrations of circulating endothelial microparticles and platelet microparticles could play a role in this target organ injury, we conducted a cross-sectional study of these markers in 3 groups: (1) untreated patients referred specifically for treatment of severe uncontrolled hypertension; (2) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
292
6
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 448 publications
(325 citation statements)
references
References 56 publications
15
292
6
5
Order By: Relevance
“…1,6,9,19 In our study, hypertensive patients displayed both elevated levels of circulating EMPs and faster baPWV, which was consistent with the earlier studies. 19,20 Therefore, it is believed that antihypertensive treatment for patients with hypertension should restore the vascular dysfunction. In our study, WCHT patients did show reduced levels of circulating EMPs and slower baPWV to some extent, indicating that pressure-lowering therapy is critical in improving vascular function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,6,9,19 In our study, hypertensive patients displayed both elevated levels of circulating EMPs and faster baPWV, which was consistent with the earlier studies. 19,20 Therefore, it is believed that antihypertensive treatment for patients with hypertension should restore the vascular dysfunction. In our study, WCHT patients did show reduced levels of circulating EMPs and slower baPWV to some extent, indicating that pressure-lowering therapy is critical in improving vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…One is because of high BP as shown by the present data and earlier report. 20 The other one may be related to inflammatory stimulation on vascular endothelium. Similar to the earlier investigations, 31,32 this study showed that the patients with hypertension had increased CRP, which is a marker for the presence of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphologic characteristics of EMPs by electron microscopy have been well described by Combes et al (11). It is now becoming apparent that EMPs provide a window to the activated endothelium in a number of disease states in which endothelial injury is central to the disease process, including atherosclerosis (16), acute coronary syndromes (17), antiphospholipid syndrome (APS) (11), thrombotic thrombocytopenic purpura (TTP) (18), multiple sclerosis (MS) (19), and most recently, hypertension (20) in adults. Moreover, plasma from patients with APS, MS, or TTP was shown to induce the formation of EMPs from endothelial cells in tissue culture (11,18,19).…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] Elevated numbers of circulating microparticles have been found in patients with a great variety of diseases with vascular involvement and hypercoagulability. [11][12][13][14][15] To the best of our knowledge, there are no reported studies that evaluated circulating microparticles in impotent diabetic men. Therefore, the aims of this study were (a) to evaluate circulating endothelial (EMP) and platelet microparticles (PMP) in diabetic men with ED, (b) to address the relation between circulating microparticles and the severity of ED and (c) to assess the relation between circulating microparticles and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%